Hypoxia-Inducible Factor-1α (HIF-1α) as a Biomarker for Changes in Microcirculation in Individuals with Systemic Sclerosis - Magdalena Maciejewska; Mariusz Sikora; Albert Stec; Michał Zaremba; Cezary Maciejewski; Katarzyna Pawlik; Lidia Rudnicka (Adis, Springer Healthcare, 2023)
Abstract Introduction Systemic sclerosis is an autoimmune disease characterized by tissue fibrosis and microangiopathy. Vascular changes such as a decrease in capillary density diminish blood flow and impair tissue oxygenation. Reliable ways to monitor disease activity and predict disease progression are desired in the process of patient selection for clinical trials and to optimize individual patient outcomes. Hypoxia-inducible factor-1 (HIF-1) is a dimeric protein complex that plays an integral role in the body's response to hypoxia. Our study aimed to investigate the potential abnormalities of HIF-1α plasma concentration and its possible association with disease activity and vascular abnormalities in patients with systemic sclerosis. Methods Blood plasma levels of HIF-1α were measured in patients with systemic sclerosis (n = 50) and in healthy individuals (n = 30) using commercially available ELISA test kits. Results The results showed a marked increase in HIF-1α levels in patients with systemic sclerosis (3.042 ng/ml [2.295-7.749]) compared to the control group (1.969 ng/ml [1.531-2.903] p < 0.01). Patients with diffuse cutaneous SSc (2.803 ng/ml, IQR 2.221-8.799) and limited cutaneous SSc (3.231 ng/ml, IQR 2.566-5.502) exhibited elevated serum HIF-1α levels compared to the control group (p < 0.01). We found a notable increase in HIF-1α plasma concentration in patients with an "active" pattern (6.625 ng/ml, IQR 2.488-11.480) compared to those with either an "early" pattern (2.739, IQR 2.165-3.282, p < 0.05) or a "late" pattern (2.983 ng/ml, IQR 2.229-3.386, p < 0.05). Patients with no history of digital ulcers had significantly higher levels of HIF-1α (4.367 ng/ml, IQR 2.488-9.462) compared to patients with either active digital ulcers (2.832 ng/ml, IQR 2.630-3.094, p < 0.05) or healed digital ulcers (2.668 ng/ml, IQR 2.074-2.983, p < 0.05). Conclusions Our results indicate that HIF-1α may serve as a biomarker in assessing microcirculatory changes in individuals with systemic sclerosis.